Anal human papillomavirus among men who have sex with men in three metropolitan cities in southern China: implications for HPV vaccination. Issue 13 (17th March 2020) - Zhou, Yiguo; Lin, Yi-Fan; Meng, Xiaojun; Duan, Qibin; Wang, Zhenyu; Yang, Bin; Zheng, Heping; Li, Peiyang; Li, Meijuan; Lu, Yong; Luo, Zhenzhou; Zou, Huachun
Abstract: Introduction: Men who have sex with men (MSM), especially those infected with human immunodeficiency virus (HIV), are at disproportionate risk for human papillomavirus (HPV) infection. Data about anal HPV prevalence among MSM in southern China are limited. Methods: MSM were recruited between January 1 and August 31, 2017 in three metropolitan cities: Guangzhou, Shenzhen and Wuxi. A self-completed tablet-based questionnaire was used to collect information about socio-demographic/sexual behavioral characteristics, history of sexually transmitted infections (STIs) and recreational drug use. An anal brush was used to collect exfoliated cells for HPV DNA testing and genotyping, and a blood sample was taken for HIV testing. Penile/anal warts were checked by a clinician. Results: A total of 536 MSM were enrolled, including 39 HIV-positive and 497 HIV-negative individuals. Compared with HIV-negative MSM, prevalence of any HPV genotype (79.5% vs 46.7%), any high-risk genotype (64.1% vs 36.6%) and any nonavalent vaccine-preventable genotype (53.9% vs 31.6%) was significantly higher in HIV-positive MSM, with all P < 0.01. HIV infection (adjusted odds ratio [AOR], 4.28; 95% confidence interval [CI], 1.87–9.80), using recreational drugs (AOR, 1.87; 95% CI, 1.22–2.87), having ≥ 3 years of sexual experience (AOR, 1.52; 95% CI, 1.01–2.28), having ≥ 6 lifetime male partners (AOR, 1.92; 95% CI, 1.29–2.86), and engaging receptive anal intercourse (AOR, 2.30; 95% CI, 1.48–3.57) were associated with higher anal HPV prevalence. Any HPV prevalence increased with age, from 24.5% at < 20 years to 55.8% at ≥ 40 years. Conclusions: Anal HPV prevalence was high among MSM in southern China, significantly associated with HIV status and sexual experience. HPV prevalence increased with age among MSM. A targeted HPV vaccination program for teenage MSM might be necessary. Our findings will inform targeted HPV modelling among MSM in China.